2019
DOI: 10.1002/bsd2.46
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory corporate social responsibility in India and its effect on corporate financial performance: Perspectives from institutional theory and resource‐based view

Abstract: The enactment of the Companies Act of 2013 in India mandating CSR spending is a regulatory pressure from the government. Institutional theory suggests that such regulatory pressure has an impact on firm heterogeneity and consequently on the competitive advantage of a firm. On the other hand, a firm's resources and capabilities like R&D expertise, advertising intensity and staff welfare& training intensity leads to firm heterogeneity and helps firm to achieve competitive advantage. So, this paper combines the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 88 publications
2
58
0
2
Order By: Relevance
“…Post the CSR mandate in India, the previous studies indicated diverse results, viz. positive (Bhagawan & Mukhopadhyayy, 2018;Gaurav, 2020), negative (Kuntluru, 2019;Bhattacharyya & Rahman, 2020) and insignificant (Dharmapala & Khanna, 2016;Nair & Bhattacharyya;Sydlowski, 2018) while examining the impact of CSR initiatives on financial performance. However, the available studies (Dharmapala & Khanna, 2016;Nair & Bhattacharyya;Sydlowski, 2018) that used CSR expenditure as a construct of CSR to examine the relationship of CSR with financial performance revealed an insignificant impact of CSR spending on financial performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Post the CSR mandate in India, the previous studies indicated diverse results, viz. positive (Bhagawan & Mukhopadhyayy, 2018;Gaurav, 2020), negative (Kuntluru, 2019;Bhattacharyya & Rahman, 2020) and insignificant (Dharmapala & Khanna, 2016;Nair & Bhattacharyya;Sydlowski, 2018) while examining the impact of CSR initiatives on financial performance. However, the available studies (Dharmapala & Khanna, 2016;Nair & Bhattacharyya;Sydlowski, 2018) that used CSR expenditure as a construct of CSR to examine the relationship of CSR with financial performance revealed an insignificant impact of CSR spending on financial performance.…”
Section: Resultsmentioning
confidence: 99%
“…Further, in the Indian context, the available literature (Bihari & Pradhan, 2011;Dhaliwal et al, 2011;Kapoor & Sandhu, 2010;Mishra & Suar, 2010) generally reported a positive effect of CSR on firm performance before the mandatory CSR regime in India. Post the CSR regulations in India, the available studies reported positive (Bhagawan & Mukhopadhyay, 2018), negative (Kuntluru, 2019) and insignificant (Dharmapala & Khanna, 2016;Nair & Bhattacharyya, 2019;Sydlowski, 2018) effect of CSR initiatives on financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these theoretical lenses are helpful to simultaneously assess the internal and external factors influencing the environmental impact of SMEs. Moreover, like all other economic sectors, the SME sector is also becoming highly competitive due to stiff competitive environment that pertain in almost every sector of the business [54].…”
Section: Theory Descriptionmentioning
confidence: 99%
“…On the other hand, KPMG in its 2018 CSR Reporting Survey reports that compliance is now "near universal" [140] (p. 1), and generally positive outcomes with regard to CSR compliance have been found [141,142].…”
Section: Hypothesis 1 (H1)mentioning
confidence: 99%